CURRENT ISSUES OF RESEARCH, DEVELOPMENT AND INNOVATION IN ROMANIA - Andreea Vass (Romanian Journal of European Affairs, 2005)
The research, development and innovation system (RDI) represents a key segment of activity, both in theory and in international practice, as an engine of social and economic progress. For Romania, the transition period has represented a major transformation step in a structural, institutional and functional perspective in association with networking with other components, so that the present configuration of the R&D system in Romania differs substantially from that of the early 1990s.